2019
DOI: 10.1002/adom.201801477
|View full text |Cite
|
Sign up to set email alerts
|

Empowered Layer Effects and Prominent Properties in Few‐Layer Metasurfaces

Abstract: applications have been realized based on the metamaterials, such as negative index materials, [3] invisibility cloaks, [4] and zeroindex materials. [5] Nevertheless, metamaterials are usually bulky, difficult to be fabricated, and suffer from high energy losses, which hinder their practical applications in modern photonic systems. In recent years, planar metasurfaces, the 2D equivalents of metamaterials, have attracted plenty of attentions due to their extraordinary abilities in controlling the polarization, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 211 publications
(301 reference statements)
0
38
0
Order By: Relevance
“…The geometry of the metasurface doublet is depicted in Figure a where the bottom layer is embedded in a low‐index glass substrate with refractive index of n sub = 1.5 while the top layer is sitting on top of the substrate in free space. The advances in nanofabrication technologies have made the fabrication of few‐layer metasurfaces feasible and several experimental realization of such metasurfaces has been demonstrated …”
Section: Dynamic All‐dielectric Metasurface Doubletmentioning
confidence: 99%
“…The geometry of the metasurface doublet is depicted in Figure a where the bottom layer is embedded in a low‐index glass substrate with refractive index of n sub = 1.5 while the top layer is sitting on top of the substrate in free space. The advances in nanofabrication technologies have made the fabrication of few‐layer metasurfaces feasible and several experimental realization of such metasurfaces has been demonstrated …”
Section: Dynamic All‐dielectric Metasurface Doubletmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] To rotate the original polarization of light, a new type of polarization rotators based on plasmonic metasurfaces has been successfully realized for transmission mode. [22][23][24][25][26][27][28][29][30] More recently, it has been reported that polarization rotators composed of properly designed metasurfaces can rotate the polarization angle of the LP light to a desired angle in the same way as can be done with optically active materials. [31][32][33][34][35][36][37][38][39] For instance, Shaltout et al proposed an optical metasurface composed of planar arrays of plasmonic nanoantennas, and the phase difference between the RCP and LCP components was generated by two sets of supercells, leading to the rotation of the polarization angle to a specific value.…”
Section: Doi: 101002/adts201900086mentioning
confidence: 99%
“…These strong chiroptical responses can be obtained by layer‐by‐layer coupling in multilayer metamaterials . For example, multilayers composed of twisted anisotropic gold nanorods are strong, broadband circular polarizers .…”
Section: Introductionmentioning
confidence: 99%